ARSENITE OXIDATION BY H2O2 IN AQUEOUS SOLUTIONS - DEPENDENCE UPON ANTHROPOGENIC INPUTS AND PHYTOPLANKTON SPECIES COMPOSITION - Pettine M.; Campanella L.; Millero F.J. (My University, 1999)
The rates of the oxidation of As(iii) with H2O2 were measured in NaCl solutions as a function of pH (7.5-10.3), temperature (10-50C) and ionic strength (I = 0.01-4). The rate of the oxidation of As(iii) with H2O2 can be described by the general expression: d[As(iii)]/dt = k[As(iii)] [H2O2] where k (mol/L-1 min-1) can be determined from (σ = +/-0.12) log k=5.29+1.41 pH-0.57I+1.40 I0.5-4898/T. The effect of pH on the rates indicates that the reaction is due to AsO(OH)2-+H2O2 k1-> products AsO2(OH)2-+H2O2 k2-> products, AsO33-+H2O2 k3-> products where k = k1 αAsO(OH)2- + k2 αAsO2(OH)2- + k3 αAsO33- and αi are the molar fraction of species i. The values of k1 = 42 +/- 20, k2 = (8 +/- 1) x 104, and k3 = (72 +/- 18) x 106 mol/L-1 min-1 were found at 25C and I = 0.01 mol/L. The undissociated As(OH)3 does not react with H2O2. The effect of ionic strength on the rate constants has been attributed to the effect of ionic strength on the speciation of As(iii). The rate expression has been shown to be valid for NaClO4 solutions, northern Adriatic sea waters, and Tiber River waters. The cations Fe2+ and Cu2+ were found to exert a catalytic effect on the rates. Cu2+ plays a role at concentration levels (>0.1 μmol/L) which are typical of polluted aquatic systems, while Fe2+ is important at levels which may be found in lacustrine environments (>5-10 μmol/L). The reaction of As(iii) with H2O2 may play a role in marine and lacustrine surface waters limiting the accumulation of As(iii) resulting from biologically mediated reduction processes of As(v).